The Process Skills Approach with Mind Map Media Through Lesson Study Improving Students’ Learning Outcomes - Annisa, Muhsinah; Abrori, Fadhlan Muchlas; alwahid, scahyo masan; Nordiansyah, Muhammad; Risma, Risma; Hasbiah, Hasbiah; Amelia, Dessy Putri; Gita, Sari Damara (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to analyze the effectiveness of mindmap-assisted process skills approach through lesson study in improving students’ learning outcomes This study uses qualitative approach with descriptive research type. The subjects of this study were students of class VB. Implementation of the lesson study cycle is carried out 13 times cycles, with details of the first lesson study model's eight cycles for the lesson study teacher and the next five cycles for the model teacher. The data collection instruments are the teachers’ learning implementation sheet and student worksheets to assess student learning outcomes in each cycle. Student learning outcomes in the implementation of lesson study by teacher model lecturers have the lowest average (54.0667) in the first LS cycle, while the highest average (71.7667) in the eighth LS cycle. So, it can be concluded that applying the mindmap-assisted process skills approach through lesson study can improve student learning outcomes.